Predicting yields using crop simulation models and gridded weather data in India - CGIAR Platform for Big Data in Agriculture (2019)
We find that gridded weather datasets vary in their representation of historic spatial and temporal temperature and precipitation patterns, creating large uncertainties in estimated crop yield responses to growing season weather. This highlights the need to consider input data uncertainty in applying crop simulation models with gridded weather data.